ANALISIS PENGARUH DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH PADA KOTA DAN KABUPATEN DI KALIMANTAN BARAT - B51107057, EKI LARASSASTY (Jurnal KIAFE, 2012)
This study aimed to examine the effect of the General Allocation Fund (DAU) and revenue (PAD) to the shopping area in the district of West Kalimantan and to detect whether the effect of DAU on shopping District / West Kalimantan greater than the effect of PAD. The sample used in this study is composed of six (6) years of research that includes eight (8) districts in West Kalimantan who reported regularly Realized Budget Report (LRA) from 2006 through 2010 to the Director General of Local Government Fiscal Balance. Data samples were analyzed using multiple linear regression previously through a classic assumption test consists of testing autocorrelation, multicollinearity, and heterocedastisity. The results of this study indicate that simultaneous DAU and PAD affects the shopping area and the two partially independent variables have positive and significant impact on the dependent variable in the form of shopping areas. Regression equation established in this study did not violate the rules of classical assumptions. There is a strong correlation and the coefficient of determination owned independent variables to the dependent variable. DAU influence far greater than the effect of PAD. This is evidence of a flypaper phenomenon in districts / cities in West Kalimantan where local governments provide greater responsiveness to increased DAU by increasing the amount of spending. Keywords: General Allocation Fund (DAU), revenue (PAD), and Expenditure